Unleashing gamification: a systematic review in primary schools - Yusri, Ahmad Afandi; Zainal, Muhammad Zuhair (Intelektual Pustaka Media Utama, 2025)
The implementation of gamification in primary education has garnered significant attention for its potential to enhance learning experiences and outcomes. This systematic review examines the integration of gamification across various subjects in primary education from 2022 to 2024, focusing on the types of strategies employed and their impacts. By analyzing 27 studies selected through the preferred reporting items for systematic reviews and meta-analyses (PRISMA) framework, this review reveals that gamification is widely applied in subjects such as language learning, mathematics, science, and many topics utilizing both digital and non-digital approaches. The findings indicate improvements in academic performance, motivation, engagement, and skill development. However, gaps remain in understanding the long-term effects, impacts on different learning styles, and potential negative consequences. Future research should explore these areas through longitudinal studies and the integration of emerging technologies in gamified learning environment.